2015
DOI: 10.1002/sia.5863
|View full text |Cite
|
Sign up to set email alerts
|

The development of near‐surface microstructures during hot rolling of aluminum–magnesium alloys in relation to work roll topography

Abstract: The effect of the work roll topography on the surface deformation of aluminum alloys during hot rolling was examined with the use of a rolling tribo-simulator. AISI 52100 steel work rolls with two surface conditions, smooth (polished to a surface roughness (R a ) of 0.01 μm) and rough (WC-coated with a surface roughness (R a ) of 5.68 μm), were used to hot roll Al-Mg alloy samples under similar conditions for a rolling schedule of 10 passes. The surface of the rolled samples reflected the work roll surface mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…This analysis thus indicated that the roughness of the work roll also has an effect on the oxide distribution and nearsurface damage depth. This agrees with previous work by Gali et al (2015), who observed deeper near-surface damage induced by the formation of larger micro-cracks when using a rough roll (5.7 µm Ra), as compared to a smooth work roll (0.01 µm Ra).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This analysis thus indicated that the roughness of the work roll also has an effect on the oxide distribution and nearsurface damage depth. This agrees with previous work by Gali et al (2015), who observed deeper near-surface damage induced by the formation of larger micro-cracks when using a rough roll (5.7 µm Ra), as compared to a smooth work roll (0.01 µm Ra).…”
Section: Discussionsupporting
confidence: 93%
“…Comparing previously reported results by Gali et al (2015) with those obtained here, a trend of increasing near-surface damage (i.e., the maximum depth of micro-cracks observed) with an increase in work roll roughness is observed. The near-surface damage, in the form of microcracks, extended to maximum depths of 1.5 µm for a 0.01 µm Ra work roll (Gali et al (2015)), 2.8 µm for the 0.1 µm Ra work roll (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations